IJCM_406A: Association between Empathy and big five personality traits among undergraduate medical students in Mangalore - Preek Arush; Jaglan Simran; Arora Aditi; Ravi Shashank; Holla Ramesh; Unnikrishnan Bhaskaran; Rekha T; Mithra Prasanna; Kumar Nithin; Motappa Rohith; Rao Mithun (Wolters Kluwer Medknow Publications, 2024)
Background: Empathy in the clinical setting is associated with satisfaction among patients, compliance to therapy and much more positive clinical outcome. This study is to determine the level of empathy among undergraduate medical students, the personality traits, according to the big five model, and to assess the association between empathy and personality traits among undergraduate medical students. Methodology: It was a descriptive study carried out among Second year MBBS students of Kasturba Medical College, Mangalore. Data was collected using Jefferson Scale of Empathy (medical student version), which is a self- administrative inventory that contains 20 questions. Mini-IPIP scale was used to measure big five personality traits, which is a 20-item short form of the International Personality Item Pool Five Factor Model. The collected data was coded and entered onto statistical package for social sciences (SPSS) version 25.0. For comparison across the group Pearson coefficient was used. Results: A positive correlation was found between the level of empathy and the personality traits of agreeableness and openness among the participants at a significant level using Pearson correlation coefficient. People with more agreeableness, indicative of sympathetic and willingness to help others are proportionately empathic. It was also found that women are more neurotic than men, which infers that women are more social and assertive than men. For openness, men are more open, imaginative and creative than women. For agreeableness, men are more cooperative and concerned than women. Women scored more than men for conscientiousness. Conclusion: The study showed a statistically significant difference in the level of empathy among the two genders, with females being more empathic than males. Between the two genders, there was a statistically significant difference among the neuroticism levels, with females being more neurotic than their male counterparts. A positive correlation was found between the level of empathy and the personality traits of agreeableness and openness among the participants.